Effects of a sleep education video on sleep knowledge and sleep habits among youth in Iceland - Ásta Gígja Elfarsdóttir 1997- (2021)
Adolescents' sleep is inadequate and in decline, negatively impacting their health and safety. This study aimed to determine whether an educational video about sleep, with the education provided in part by celebrity role models, could impact sleep knowledge and sleep habits among youth. In total, 36 Icelandic junior college students aged 18–20 years participated in the study. Participants were assigned to an intervention group (n = 22), subjected to a sleep education video, and a control group (n = 14). Sleep knowledge and sleep habits were assessed before and two weeks after the intervention using the Pittsburgh Sleep Quality Index (PSQI), a sleep habit questionnaire, and a sleep knowledge questionnaire. Baseline data demonstrated prevalent sleep problems (63.9% poor sleep (PSQI > 5), 55.6% insufficient sleep on weekdays (< 7 hr) and 80.6% irregular weekday-weekend rise times (> 2 hr)). Mann-Whitney analysis revealed significant effects on sleep knowledge for the intervention group compared to the control group post-intervention (p = .005); however, no significant effects on sleep habits were detected. To conclude, the sleep education video successfully promoted sleep knowledge; yet, other measures may have to be taken in conjunction with sleep education to see long-term improvements in sleep habits. Keywords: sleep education, sleep habits, sleep knowledge, video education, role models Svefn ungmenna er ófullnægjandi og fer versnandi, sem hefur neikvæð áhrif á heilsu þeirra og öryggi. Markmið þessarar rannsóknar var að ákvarða hvort fræðslumyndband um svefn, þar sem þekktar fyrirmyndir veita hluta fræðslunnar, gæti haft áhrif á svefnþekkingu og svefnvenjur ungmenna. Í heildina tóku 36 íslenskir menntaskólanemar á aldrinum 18–20 ára þátt í rannsókninni. Þátttakendum var skipt í tilraunahóp (n = 22), sem horfði á fræðslumyndband um svefn, og samanburðarhóp (n = 14). Svefnþekking og svefnvenjur voru metin fyrir og tveimur vikum eftir inngrip með Pittsburgh Sleep Quality Index (PSQI), spurningalista um ...